Court of the Moon, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
One of the imposing South Towers, entrance to the Homes and Gardens Building at the Golden Gate International Exposition on Treasure Island, San Francisco Bay. In foreground, Treasure Garden and its central pool.